Internal magnetic finishing of micro hole for aerospace component - Gan, Justin Ewei (2017)
Today, the aviation industry is one of the fastest growing sectors of the world’s economy, leading to a great demand for aircraft which greater fuel efficiency to travel further. This has led to the development of new powerful aircraft engines which operate at high temperatures to ensure efficiency. One of the areas which needs to be improved is the efficiency of heat removal of the engine turbine compressor blades. A solution for this involves micro holes being built into the blades to increase the rate of heat loss through convection. To achieve the best possible airflow efficiency, the internal walls of the micro holes require good internal surface finishing. Currently, there are limited internal finishing technologies available for small sized holes, especially so for complex geometries. Therefore new process technology is needed for the internal finishing of these complex holes. The objective of this project is to investigate the development of a novel micro internal finishing technology using a magnetic field for micro passage. This project will focus on evaluating the feasibility of applying the Internal Magnetic Finishing technique on a straight SUS 304 stainless steel pipe. The experimental parameters will be varied through different experiments, to identify the best possible combination to maximise the efficiency of the Internal Magnetic Finishing technique. The capability of the Internal Magnetic Finishing technique will then be evaluated through the observation of the amount of material removed and the surface roughness. In conclusion, the Internal Magnetic Finishing technique can be used for the surface enhancement of the internal surfaces of the stainless steel pipes. Further research has to be done on the application of the Internal Magnetic Finishing technique on other aerospace materials. It can also be further tested on the various combinations of the parameters such as the ratio of rod diameter to the inner diameter of the workpiece and workpiece geometry.